Herpetofauna of the Cerro Guiengola, Isthmus of Tehuantepec, Oaxaca - Martín-Regalado, Cintia Natalia; Gómez-Ugalde, Rosa Ma.; Cisneros-Palacios, Ma. Emma (Instituto de Ecología, A.C., 2011)
This study was performed in Cerro Guiengola in the Mexican state of Oaxaca, located in the Isthmus of Tehuantepec, with the objective of contributing to the knowledge on herpetofauna located in that area; 103 collections and 602 visual records of amphibians and reptiles were made during 60 days of field work, and 40 species belonging to 32 genera and 18 families are listed in this study. Based on the data collected, the herpetofauna distribution in Cerro Guiengola was classified according to altitude, vegetation and microhabitat. Vegetation and microhabitat similarity dendograms were made using Jaccard’s method. Some species were reported in altitudes and vegetation types different from those cited in the literature. Simpson and Shannon-Wiener’s indices of diversity show that the study area varies according to the obtained data; 13 species out of the 40 species recorded are endemic to Mexico and 3 to Oaxaca; 42.5% of the reported herpetofauna are listed in the NOM-059-COL-2001 and 47.5% by the International Union for the Conservation of Nature (IUCN).